The Impact of Digital Burnout on Organizational Citizenship Behavior (OCB) among Remote Workers - Nurhayati, Aliah; Zamzami, Shidqi; Jannah, Lia Nur (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
The development of digital technology has transformed the work landscape, especially with the increasing prevalence of remote work systems in Indonesia’s digital sector. However, the high intensity of technology use in the remote work context also poses the risk of digital burnout, which is mental and emotional exhaustion due to excessive exposure to technological demands. This phenomenon potentially affects employee behavior, including extra-role behaviors known as Organizational Citizenship Behavior (OCB). This study aims to explore the relationship between digital burnout and OCB among remote workers in the digital sector, while also understanding how technological pressure influences work dynamics and employee contributions beyond formal tasks. The research method uses a quantitative approach with purposive sampling technique, targeting 150 to 300 remote workers who work at least three days per week and heavily rely on digital platforms such as Zoom, Slack, and Google Workspace in their daily activities. Data were collected through online surveys and analyzed using SmartPLS to test the relationships between variables with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that although digital burnout is quite prevalent, employees still demonstrate positive OCB, indicating the presence of adaptation mechanisms and strong organizational commitment. These findings enrich the understanding of how remote workers manage technological pressure while maintaining extra contributions in a dynamic digital work environment. The contribution of this study lies in providing new insights into the interaction between digital burnout and OCB in the digital work era, as well as practical implications for human resource management in designing strategies to support the well-being and productivity of remote employees. This study encourages the development of more humane and sustainable work policies in facing the challenges of digital transformation.